2002
DOI: 10.1128/jcm.40.11.4131-4137.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibodies Directed against Human Herpesvirus 6 U94/REP in Sera of Patients Affected by Multiple Sclerosis

Abstract: The association between human herpesvirus 6 (HHV-6) and multiple sclerosis (MS) is controversial. In fact, it is difficult to establish a causative role of HHV-6, due to the high prevalence of latently infected individuals in the healthy population. Therefore, the presence of virus sequences in tissue biopsy does not support a viral role, and serological assays do not show significant differences between MS patients and control populations. The only viral gene expressed during latency is U94/rep. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…The same is true for reports on an altered humoral or tissue-specific immune response in MS patients (expressed as serum IgM or CSF IgG levels or lymphoproliferative responses towards HHV-6 antigens) (63,74,119,368,370,397). In one study, higher prevalence and higher antibody titers towards HHV-6 pU94 were found and it was concluded that MS patients may undergo a different exposure to HHV-6 than controls (56). Several authors who found HHV-6A more prevalent than HHV-6B have pointed at the importance of subtyping HHV-6-positive cases (7,13,208,370).…”
Section: Clinical Manifestations Of Hhv-6 Infectionmentioning
confidence: 79%
“…The same is true for reports on an altered humoral or tissue-specific immune response in MS patients (expressed as serum IgM or CSF IgG levels or lymphoproliferative responses towards HHV-6 antigens) (63,74,119,368,370,397). In one study, higher prevalence and higher antibody titers towards HHV-6 pU94 were found and it was concluded that MS patients may undergo a different exposure to HHV-6 than controls (56). Several authors who found HHV-6A more prevalent than HHV-6B have pointed at the importance of subtyping HHV-6-positive cases (7,13,208,370).…”
Section: Clinical Manifestations Of Hhv-6 Infectionmentioning
confidence: 79%
“…In several retrospective studies, MS patients have significantly higher EBV IgG titres than healthy controls (Table 3), which is also the case in studies on HHV-6 [28,[47][48][49] and endogenous retrovirus [50]. This has been interpreted as an involvement of these viruses in MS, but it is important to notice that MS patients have also increased IgG titres against other viruses, such as measles virus, which is not involved in the disease [6].…”
Section: Detection Of Antibodies In Bloodmentioning
confidence: 91%
“…As indicated previously, the presence and amount of U94 transcripts might reflect episomal latency and, in some cases, ciHHV-6. Moreover, a recombinant U94 protein has been used to create an ELISA that would be suitable for exploring the antiviral immune response in HHV-6-related chronic diseases (141). However, the relevance of U94-related markers remains to be demonstrated formally.…”
Section: Latent Infectionmentioning
confidence: 99%
“…Among them, HHV-6 appears to be one of the most serious candidates in the category of infectious triggers, on the basis of immunological, virological, and experimental data (6). These data include the isolation of this virus from diseased CNS tissues of MS patients, serologic studies of HHV-6 antibody reactivity in their sera and CSF, and in situ detection of HHV-6 DNA transcripts (141,183,(185)(186)(187)(188). This hypothesis also results from general considerations founded on the neurotropism of the virus combined with its theoretical capacity to induce both neuroinflammation and autoimmunity.…”
Section: Chronic Infectionsmentioning
confidence: 99%